O controvertido projeto de lei que regulamenta o licenciamento ambiental: o dilema entre o progresso econômico e o retrocesso ambiental - Santos, Jamile de Lima (Universidade Federal Rural do Semi-Árido, 2019)
Environmental licensing is configured as a management tool in the prior control of environmental quality and in the assessment of the risk of environmental degradation. From the point of view of the regulatory framework, environmental licensing is required for activities that use environmental resources that present an actual or potential ecological risk. That said, Bill No. 3,729 / 04, which is being processed in the National Congress, in the effort to 'improve' licensing, presents new regulations under the justification of modernizing environmental management in the country. In this context, the objective of the study is to analyze the proposition of new legal rules that establish the exemption of licensing, the inexigibility of environmental technical studies, the insertion of new categories of environmental license and the repeal of the guilty modality of the crime of license in disagreement with environmental standards. It is concluded that the legislative proposal weakens the first protective function of environmental licensing, since it leaves doubts as to what way national environmental management should follow: economic progress or environmental regression. The answers to the questions raised indicate that the legislator has not complied with the principles of Precaution, Prevention and Prohibition of Retraction of Environmental Law and are also unconstitutional with regard to the fundamental right to an ecologically balanced environment.
Artigo Acadêmico
Keywords: Licenciamento ambiental; Marco regulatório; Princípios ambientais; Progresso econômico; Retrocesso ecológico; Environmental licensing; Regulation mark; Environmental principles; Economic progress; Ecological retraction; CIENCIAS SOCIAIS APLICADAS::DIREITO